2011
DOI: 10.1007/s10725-011-9563-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of oxidative and antioxidative events during dehydration and rehydration of resurrection plant Ramonda nathaliae

Abstract: In order to investigate changes of oxidative status in relation to the activity of the various protective mechanisms in resurrection plant Ramonda nathaliae, we have analysed time and relative water content (RWC) related changes in lipid peroxidation and ion leakage, hydrogen peroxide accumulation, changes of pigment content and antioxidative enzyme activity, together with expression of dehydrins. The results indicate that enhanced oxidative status during dehydration, not previously reported for resurrection p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 41 publications
1
39
0
Order By: Relevance
“…Degl'Innocenti et al (2008) showed that in R. serbica, the RWC decreased from values of 97 % in fully hydrated control plants to values of only 7 % after 2 weeks dehydration. In addition, the RWC of R. nathaliae decreased from 94.5 % to 3.6 % during dehydration (Jovanoviç et al 2011). Kinetics of relative water content during dehydration-rehydration cycle was reported from other authors in R. serbica (Augusti et al 2001;Quartacci et al 2002;Veljovic-Jovanoviç et al 2006;Sgherri et al 2004) and Haberlea rhodopensis (Nagy- Deri et al 2011;Mihailova et al 2011;Djilianov et al 2011;Georgieva et al 2010).…”
Section: Relative Water Contentsupporting
confidence: 59%
See 1 more Smart Citation
“…Degl'Innocenti et al (2008) showed that in R. serbica, the RWC decreased from values of 97 % in fully hydrated control plants to values of only 7 % after 2 weeks dehydration. In addition, the RWC of R. nathaliae decreased from 94.5 % to 3.6 % during dehydration (Jovanoviç et al 2011). Kinetics of relative water content during dehydration-rehydration cycle was reported from other authors in R. serbica (Augusti et al 2001;Quartacci et al 2002;Veljovic-Jovanoviç et al 2006;Sgherri et al 2004) and Haberlea rhodopensis (Nagy- Deri et al 2011;Mihailova et al 2011;Djilianov et al 2011;Georgieva et al 2010).…”
Section: Relative Water Contentsupporting
confidence: 59%
“…Previous investigation of R. serbica and R. nathaliae has brought the evidence to adaptive features necessary to preserve cell membrane integrity (Quartacci et al 2002), antioxidative capacity (Sgherri et al 2004;Jovanoviç et al 2011), photosynthetic activity (Tuba et al 1998), CO 2 fixation and chlorophyll a fluorescence (Degl'Innocenti et al 2008), genome size variation and polyploidy (Siljak-Yakovlev et al 2008), osmotic adjustment (Zivkoviç et al 2005), seed germination (Gashi et al 2012a) and in vitro cultivation from seeds of Ramonda plants (Kongjika et al 2002;Gashi et al 2011;Dontcheva et al 2009;Daskalova et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…In angiosperm resurrection plants, genes encoding antioxidant enzymes are either constitutively expressed or induced by drought (;50% RWC), particularly desiccation (Dinakar and Bartels, 2012;Gechev et al, 2013;Farrant et al, 2015). In the angiosperm resurrection species Ramonda nathaliae (an HDT), a time-course analysis of different antioxidant enzyme activities revealed the sequential involvement of these enzymes in dehydration and subsequent rehydration (Jovanovic et al, 2011).…”
Section: Mechanisms For Longevity In the Dry Statementioning
confidence: 99%
“…In Arabidopsis seeds and X. viscosa leaves, LEA proteins are broadly distributed in subcellular compartments, reflecting their protective role in the various cellular membranes (Candat et al, 2014;Costa et al, 2017). LEA genes are dehydration inducible and are constitutively expressed in resurrection species (Rodriguez et al, 2010;Jovanovic et al, 2011;Gechev et al, 2013;Giarola et al, 2015a;Costa et al, 2017). The expression of LEA genes from C. plantagineum increases upon early or partial dehydration (Rodriguez et al, 2010;Giarola et al, 2015a).…”
Section: Mechanisms For Longevity In the Dry Statementioning
confidence: 99%
“…In recent study, the resurrection plants from Ramonda genus have become important models for studying drought tolerance (Quartacci et al 2002;Veljovic-Jovanovic et al 2006;Gashi et al 2013a), photosynthetic abilities during transition from anabiosis (Augusti et al, 2001;Degl'Innocenti et al 2008;Gashi et al, 2013a), antioxidative capacity (Sgherri et al 2004;Jovanovic et al 2011) and other specialized and multidisciplinary studies. Other authors have reported a genetic (polyploidy) and morphologic diversity within and between plants of genus Ramonda populations (Siljak-Yakovlev et al 2008;Daskalova et al 2012;Gashi et al 2013b;Gashi 2013).…”
Section: Introductionmentioning
confidence: 99%